A new method for generating cryptographically strong sequences of pseudo random bits for stream cipher - Khalifa, Othman Omran; Abumuala, Mohammed; Hassan Abdalla Hashim, Aisha (2010)
The increasing privacy risks associated with the recent growth of multimedia streaming applications raised a big industry demand for secure and efficient stream cipher. The fact that stream ciphers do not expand messages, and tolerant to biterrors, make it highly desirable for many communication applications. During the last one and half decade several cryptosystems have been put forward, many of them have been more or less attacked. In one of the stages of stream cipher’s development, it is required to design a cryptographically strong pseudo random bit generator (PRBG). In this paper a new method for generating secure sequences of pseudo random Bits for stream cipher using random map is presented, detailed statistical results of the generated bit sequences is showed, and finally a comparison with a true random sequence results is done.